Global Quality Management: A Research Focus - Kim, Kee Young (Institutional Knowledge at Singapore Management University, 1995)
This study looks at the purchasing of imported industrial products among managers in a newly industrializing country (NIC). The authors propose that the industrial marketing requirements to buyers in an NIC, given their mix of environmental and organizational conditions, are different from those in advanced nations. South Korea, in addition to being a representative NIC, is interesting from the standpoint that there is a heavy import dependence on Japan. The results of a survey of South Korean companies importing industrial products in key representative industries suggest that the strong ratings for Japanese industrial products are based not only on stronger overall quality, but also on their higher orientation toward intangible factors such as communication, technical assistance, and reliability. Moreover, many of the Japanese sources have “localized” their product to compete with the domestic suppliers as well. These results suggest that in order to improve their performance, other foreign suppliers must compete on dual fronts; a product-related dimension as well as a more service-related dimension. Other possible avenues for improvement can be found by examining differences in supplier ratings based on organizational and situational influences. This study shows that buyers in smaller and newer companies tend to be more open to non-Japanese products. The findings also suggest that certain technology-transfer modes may be more conducive to generating better supplier ratings. Overall, the variability of country ratings across situational factors strongly indicates that more conceptualization and theory building is needed in the international industrial marketing area.